Modern tendencies of the world market IT-outsourcing services - Кошкарьова, Єлизавета Леонідівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
In this article the distinctive features of outsourcing as a service and the purpose of its use; the economic essence of outsourcing is to construct a system of relations between organizations that transmit and receive over the execution of certain activities on the basis of concluded long-term contracts; the basic segments of the modern world outsourcing market - outsourcing information technology (IT-outsourcing) and business process outsourcing (BPO-outsourcing), their features, growth rates, and the practical results of outsourcing. Identified consequences of high demand for outsourcing services in the field of high technology and R & D that lead to transformation outsourcing business process to knowledge management outsourcing (well known as Knowledge Process Outsourcing, KPO). The dynamics and identifies current trends in the world market outsourcing market was analyzed. Special attention was paid to definition leading countries in terms of spending on business process outsourcing, searching major suppliers and consumers of IT outsourcing in the world and overview benefits of using IT-outsourcing and business process outsourcing, in conditions of finding the best ways to improve the competitiveness of Ukrainian economy. A general conclusion is made concerning global outsourcing market knowledge-intensive high-tech services is a global mechanism for interaction with entities on the implementation of agreements. The subject these agreements are the intellectual services. The major market trends include dynamic growth, strengthening and increasing competition, attracting new countries and regions, the emergence of new entrants and the increased demand for high-tech services.